Innate immune checkpoint inhibitor resistance is associated with melanoma sub-types exhibiting invasive and de-differentiated gene expression signatures - Hossain, Sultana Mehbuba; Gimenez, Gregory; Stockwell, Peter A.; Tsai, Peter; Print, Cristin G.; Rys, Janusz; Cybulska-Stopa, Bozena; Ratajska, Magda; Harazin-Lechowska, Agnieszka; Almomani, Suzan; Jackson, Christopher; Chatterjee, Aniruddha; et al. (Frontiers in Immunology, 2022)
Melanoma is a highly aggressive skin cancer, which, although highly immunogenic, frequently escapes the body’s immune defences. Immune checkpoint inhibitors (ICI), such as anti-PD1, anti-PDL1, and anti-CTLA4 antibodies lead to reactivation of immune pathways, promoting rejection of melanoma. However, the benefits of ICI therapy remain limited to a relatively small proportion of patients who do not exhibit ICI resistance. Moreover, the precise mechanisms underlying innate and acquired ICI resistance remain unclear. Here, we have investigated differences in melanoma tissues in responder and non-responder patients to anti-PD1 therapy in terms of tumour and immune cell gene-associated signatures. We performed multi-omics investigations on melanoma tumour tissues, which were collected from patients before starting treatment with anti-PD1 immune checkpoint inhibitors. Patients were subsequently categorized into responders and non-responders to anti-PD1 therapy based on RECIST criteria. Multi-omics analyses included RNA-Seq and NanoString analysis. From RNA-Seq data we carried out HLA phenotyping as well as gene enrichment analysis, pathway enrichment analysis and immune cell deconvolution studies. Consistent with previous studies, our data showed that responders to anti-PD1 therapy had higher immune scores (median immune score for responders = 0.1335, median immune score for non-responders = 0.05426, p-value = 0.01, Mann-U-Whitney two-tailed exact test) compared to the non-responders. Responder melanomas were more highly enriched with a combination of CD8+ T cells, dendritic cells (p-value = 0.03) and an M1 subtype of macrophages (p-value = 0.001). In addition, melanomas from responder patients exhibited a more differentiated gene expression pattern, with high proliferative- and low invasive-associated gene expression signatures, whereas tumours from non-responders exhibited high invasive- and frequently neural crest-like cell type gene expression signatures. Our findings suggest that non-responder melanomas to anti-PD1 therapy exhibit a de-differentiated gene expression signature, associated with poorer immune cell infiltration, which establishes a gene expression pattern characteristic of innate resistance to anti-PD1 therapy. Improved understanding of tumour-intrinsic gene expression patterns associated with response to anti-PD1 therapy will help to identify predictive biomarkers of ICI response and may help to identify new targets for anticancer treatment, especially with a capacity to function as adjuvants to improve ICI outcomes.